1997
DOI: 10.2527/1997.7571764x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body composition at selection on reproductive development in large white gilts.

Abstract: Fifty-four Large White gilts were used to determine the effect of body composition at selection (145 d of age) on the onset of puberty and subsequent reproductive development until 202 d of age. Gilts were assigned to one of three groups based on their backfat depth at selection: 10 to 12 mm (L), 13 to 15 mm (M), and 16 to 18 mm (F). All of the F gilts, 92% of the M gilts, and 67% of the L gilts reached puberty by slaughter at 202 d of age. Data from a subgroup (first 67% to reach puberty in each group; L = Lp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
1
25
0
8
Order By: Relevance
“…It has been postulated that a certain level of body condition is necessary for puberty attainment in gilts (Gaughan et al, 1997), whereas dietary treatments do not seem to affect pubertal age (Patterson et al, 2002). However, gilts with greater growth rate and backfat have shorter weaning to estrus intervals (Tummaruk et al, 2001) and age at puberty is positively genetically correlated with weaning to estrus interval and signs of estrus (Sterning et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that a certain level of body condition is necessary for puberty attainment in gilts (Gaughan et al, 1997), whereas dietary treatments do not seem to affect pubertal age (Patterson et al, 2002). However, gilts with greater growth rate and backfat have shorter weaning to estrus intervals (Tummaruk et al, 2001) and age at puberty is positively genetically correlated with weaning to estrus interval and signs of estrus (Sterning et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The level of protein deposition is considered to be the regulator of reproduction functions in gilts. Gaughan et al (1997) reported that the level of fat and protein deposition was bound to the physiology of sexual maturity and it was considered to be a more important determinant for achieving puberty than age and weight. Čeřovský (2001), Bečková and Daněk (2002), Čechová and Tvrdoň (2002) found out a positive influence of gain on reproduction ability.…”
mentioning
confidence: 99%
“…Vários autores sugerem que animais selecionados para maior deposição de tecido magro podem apresentar maturação reprodutiva mais tardia (Gaughan et al, 1997;Evans & O'Doherty, 2001;Wettere et al, 2006). É provável que o genótipo usado no presente estudo tenha maturação fisiológica do eixo-hipotálamo-hipófise-gônadas mais tardia do que outros genótipos modernos, o que explicaria os baixos percentuais de manifestação da puberdade observados nas leitoas estimuladas aos 150 e 170 dias de idade.…”
Section: Resultsunclassified